2019
DOI: 10.1021/acs.jmedchem.9b01293
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 6-(2,4-Dichlorophenyl)-5-[4-[(3S)-1-(3-fluoropropyl)pyrrolidin-3-yl]oxyphenyl]-8,9-dihydro-7H-benzo[7]annulene-2-carboxylic acid (SAR439859), a Potent and Selective Estrogen Receptor Degrader (SERD) for the Treatment of Estrogen-Receptor-Positive Breast Cancer

Abstract: More than 75% of breast cancers are estrogen receptor alpha (ERα) positive (ER+), and resistance to current hormone therapies occurs in one-third of ER+ patients. Tumor resistance is still ERα-dependent, but mutations usually confer constitutive activation to the hormone receptor, rendering ERα modulator drugs such as tamoxifen and aromatase inhibitors ineffective. Fulvestrant is a potent selective estrogen receptor degrader (SERD), which degrades the ERα receptor in drug-resistant tumors and has been approved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…2A-D). These biological observations are in agreement with SAR439859 inducing conformational change in helix 12 of the ERa (53).…”
Section: Discussionsupporting
confidence: 88%
“…2A-D). These biological observations are in agreement with SAR439859 inducing conformational change in helix 12 of the ERa (53).…”
Section: Discussionsupporting
confidence: 88%
“…This study mainly analyzes the clinical therapeutic effect of sequential therapy with tamoxifen (TAM) and letrozole (LTZ) versus LTZ monotherapy in the treatment of BC. It is shown that the tumor tissue of most BC patients is estrogen-dependent, and inhibiting estrogen stimulation of tumors can help to curb cancer progression [ 7 ]. Both TAM and LTZ are common antiestrogen drugs in clinic [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amcenestrant antagonizes the binding of E2 to ER but also promotes the transition of ERα to an inactive conformation that leads to up to 98% receptor in in vitro assays. These dual properties lead to a deeper inhibition of ERα pathways and a more effective antiproliferative activity in ERα-dependent BC cell lines driven by mutant or wild-type ERα compared to other ERα inhibitors [82,83].…”
Section: Sar439859 (Amcenestrant)mentioning
confidence: 99%